Xylem Vessels Traits of Oil Palm Roots Influenced by Root Diameter and Soil Hydrological Regime - Amanatun Nisa; Triadiati Triadiati; Sulistijorini Sulistijorini; Martyna M Kotowska (HAYATI Journal of Biosciences, 2024)
Oil palm has been widely studied regarding growth and development, water use, productivity, and other economically relevant functions. However, not much is known about the hydraulic conductivity of oil palm root systems and how xylem vessels perform their function to transport water from roots to shoots so far. This information is needed to describe oil palm strategies to maintain water status, especially in oil palms that grow under various soil hydrological regimes. To investigate the root hydraulic performance, we measured mean xylem vessel diameter (D), vessel density (VD), vessel lumen area (Alumen), and potential hydraulic conductivity (Kp) for oil palm root samples in seasonally flooded riparian and well-drained sites at Harapan Jambi Forest. The result showed that D, Alumen, and Kp increased with increasing root diameter at both plantation types. On the contrary, VD significantly decreased with increasing root diameter. Potential hydraulic conductivity (Kp) in riparian sites was smaller than in well-drained sites and significantly different in root diameter >2-5 and >5-10 mm and related to both plantation types. The low potential hydraulic conductivity of root xylem vessels and the narrowing of xylem vessel lumen that occurs in oil palm roots in the seasonally flooded riparian sites were presumed as adaptation mechanisms to maintain water supply from the roots to the shoot in oil palm plants in these sites.